COVID-19 Vaccines for the low-income Countries; challenges and the way forward - Adhikari, Purushottam; Poudel, Sangeeta; Itani, Asmita; Gautam, Swotantra; Yadav, Saroj Adhkari (Journal of Gandaki Medical College-Nepal, 2021)
The vaccine rollout has started for the health workers as well as common people all around the world. The production has been going on rapidly, but the poor and low income countries are still lagging behind to get in the vaccine race and have their people vaccinated. A group of several international non-governmental organizations have warned about 90% of people in 67 low-income countries to have a low chance of being vaccinated in 2021 due to more than a necessary number of vaccines reserved by developed countries. COVAX program, co-led by Gavi, the Vaccine Alliance, along with the World Health Organization (WHO) and the Coalition for Epidemic Preparedness Innovations (CEPI) has raised rays of hope but it’s still long way to go. Vaccine hesitancy among the public, logistics and storage difficulty and emergence of new variants has emerged as potential challenges for COVID-19 vaccination in developing countries.